Weed Management and Soybean Yields as Influenced by Row Width and Post-Emergent Herbicide Application Timing - S. R. Duncan; E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2020)
Irrigated soybeans were grown in 2018 and 2019 at the Kansas River Valley Experiment Field near Rossville, KS. Soybeans were planted in 30-inch or 15-inch rows and a standard pre-emergent herbicide was applied. Planting dates were May 11 and June 4 in 2018 and 2019, respectively. The post-emergent herbicide was applied at approximately 21 or 35 days following soybean planting (DAP). Weed control and crop injury were visually evaluated approximately every seven days following herbicide application. Yields, moisture, and test weights were calculated from the center two rows in 30-inch plots and four rows in 15-inch plots after combine harvest. Predominant weeds present were Palmer amaranth, giant foxtail, ivyleaf morningglory, and honeyvine milkweed. Soybean yields from plots without post-emergent herbicide applied were reduced 6–17% vs. those that were treated. In the 27-day longer growing season of 2018, yield of soybeans planted in 15-inch rows trended slightly, though not significantly, higher than those planted in 30-inch rows.
Keywords: soybeans; weed management; row width; herbicide timing; irrigation